Reinforcing the involvement of students in learning business economics through active methodologies and student response systems - Izagirre-Olaizola, Julen; Morandeira-Arca, Jon; Mitxeo-Grajirena, Jone; Mendizabal-Zubeldia, Alaitz; Lertxundi-Lertxundi, Aitziber (Journal of Management and Business Education, 2020)
This work gathers an experience carried out during the academic years 2018-2019 and 2019-2020 in the Degree in Business Administration and Management in the Faculty of Economics and Business of the University of the Basque Country/Euskal Herriko Unibertsitatea (Gipuzkoa section). The main objective of the essay is to reinforce the involvement of students in the learning process and, secondly, to collect their perception of active methodologies for teaching-learning and thus be able to improve their application. To this end, we have used resources that employ the students' mobile phones, specifically the Socrative tool, to respond to online questionnaires, with the aim of reinforcing the motivation and participation of the students, and in the general context of the inverted classroom methodology.